Answer:
= 78
= 3.5
Step-by-step explanation:
First we need to find .
We can use the equation to solve for .
We can then change that equation to , since the Commutative Property of Addition says that you can have any addition in any order.
Now, we can solve the equation.
Now that we solved , we can now solve for .
Since 25 equals , we can solve the equation .
Here is how you solve it:
Since equals 3.5, which is the simplest form, that is the answer.
Hope this helps, and please mark me brainliest! :)
Answer: i think it’s no real solutions
Step-by-step explanation:
Answer:
14
Step-by-step explanation:
It's just that simple man.
Answer:
54 beads
Step-by-step explanation:
1 hexagon = 6
2 hexagons = 10
3 hexagons = 14
Based on the pattern shown above +4 you can create an equation from this to help support finding the amount.
y = 4x + 6
y - total amount
4x - amount that is added by
6 - initial amount for 1 hexagon
Based on this you plug in 12 into x and you will find the answer:
y = 4(12) + 6
= 48 + 6
= 54
If you need to check the work honestly drawing it out, but this equation can also be supported based on the 3rd diagram of hexagon, where the initial is 6 and then 4 are added each time afterwards!!!